P252 PROTOCOL FOR TELEHEALTH MANAGEMENT AND STRATIFICATION RISK OF ELDERLY PATIENTS WITH CHRONIC HEART FAILURE DURING THE COVID–19 PANDEMIC: A MID–TERM PROGNOSTIC EVALUTATION BY TELEHFCOVID–19 SCORE. (18th May 2022) - Verga, F; Orso, F; Herbst, A; Camartini, V; Virciglio, S; D'Errico, G; Salucci, C; Di Bari, M; Marchionni, N; Ungar, A; Fattirolli, F; Baldasseroni, S
Abstract: Introduction: The Coronavirus Disease (COVID–19) pandemic and its consequences has forced physicians to develop telematic methods in order to follow up patients with cronic diseases, such as heart failure (HF). Objectives: To evaluate TeleHFCovid–19 score as a mid–term (six months) prognostic score in terms of prediction of hospitalitazion and cardiovascular mortality in patients with chronic HF during Covid–19 pandemic. Methods: During COVID–19 pandemic (from March 2020 to May 2020), we were forced to cancel nearly all follow–up checks in our HF outpatient clinic. We hence standardized a telephone follow–up by developing a questionnaire (Fig. 1 ) from which we then obtained a score, later called the "TeleHFCovid–19 score" (0–29). This score stratified patients in three risk score groups: green (0–3), yellow (4–8), and red (≥9), for which the next telefonic evaluation was planned after 4, 2 and 1 weeks, respectively. Results: 146 patients were enrolled: 112 were classified as green, 21 as yellow and 13 as red. Mean age was 81 years, females were 40%. Approximately one third had EF < 40%. At six months, compared to red (69.2%) and yellow patients (33.3%), green patients (8.9%) presented a significantly lower rate of the composite outcome of cardiovascular death and/or HF hospitalization, (p < 0.001, Fig 2 ). Multivariate analysis showed that high levels of creatinine (OR 5.960, 95% CI 1.627–21.837, p = 0.007), dyspnea at rest or for basic activities (OR 2.469, 95% CI 1.216–5.013, p = 0.012) and a high loop–diuretic dosage (OR 6.224, 95% CI 1.504–25.753, p = 0.012) were indipendently associated with the outcome. Moreover, ROC analysis showed a high sensibility and specificity for our score at six months (AUC =0.789, 95% CI 0.682–0.896, p < 0.001), with a score < 4.5 (very close to the green group cut–off) that identified lower–risk subjects (Fig 3 ). Conclusions: The TeleHFCovid–19 score was able to correctly identify patients with good outcomes at six months. Furthermore, it has the ability to stratify the adverse event risk and this could represent a useful tool to appropriately schedule the reevaluation timing of these patients and to identify those who may need urgent hospital evaluation.